S130 Multicomponent and longitudinal analysis of patients with difficult-to-treat asthma and severe asthma reveal near absence of T2-low status. (11th November 2022) - Rupani, H; Kyyaly, A; Azim, A; Barber, C; Howarth, PH; Haitchi, HM; Kurukulaaratchy, RJ
Abstract : Background: Airway inflammation in asthma is heterogenous and frequently described as type 2-inflammation (T2) high or T2-low. The identification of T2-high disease is important as it has prognostic and therapeutic implications but its prevalence in patients with difficult-to-treat and severe asthma (SA) is unclear. Aims: Understand the prevalence of T2-high asthma in this group of patients using a multicomponent definition that includes blood and exhaled biomarkers and incorporates longitudinal peripheral blood eosinophil (PBE) measurements. Methods: 388 biologic naïve patients from the Wessex Asthma Cohort of difficult asthma (WATCH) 1 study were evaluated. T2-high asthma was defined as FeNO≥20ppb and/or PBE ≥150 cells/ul and/or need for maintenance OCS (mOCS) and/or clinically allergy driven asthma (skin prick test positive alongside symptoms with exposure). 2 Results: T2-high asthma was identified in 93% (360/388) of patients using the multicomponent assessment: 53% had raised FeNO, 66% had raised PBE, 30% were on mOCS (only 7 patients identified solely based on this criteria) and 51% had clinically allergen driven symptoms. BMI (median 29.6 vs 29.3), ICS dose (1500 mcg BDP vs 1500 mcg BDP, [IQR 2000]), exacerbations (requiring OCS treatment and/or hospital admission) and presence of comorbidities commonly associated with asthma (GORD, rhinitis, breathing pattern disorder, anxiety) were similar in patients classified as T2-high or T2-low. T2-high patients had worse airflow limitation compared to T2-low patients (FEV1 /FVC 65.9% vs 74.6% p=0.04). Of the 7% (28/388) patients who did not fit criteria for T2-high asthma, 21 patients (75%) had evidence of raised PBE within the preceding 10 years- leaving only 7 patients overall (1.8%) who did not have a current or historical T2-signal. Incorporation of sputum eosinophilia ≥2% into the multicomponent definition in a subset of 117 patients with induced sputum data found, similarly, that 96% (112/117) met criteria for T2-high asthma (69/117, 59% had sputum eosinophils ≥2%). Conclusion: Almost all patients with difficult-to-treat and SA have T2-high disease with <2% of patients displaying absence of any current or historical T2-defining criteria. References: Azim A, et al. BMC Pulm Med 2019 Global Initiative for Asthma 2021.